Evaluation of the Clinical Effects and Frequency of MEFV Gene Mutation in Patients with Inflammatory Bowel Disease - S. Sahin (Hindawi Limited, 2021)
Background. The clinical and pathological features of inflammatory bowel disease (IBD) and Familial Mediterranean Fever (FMF) are similar. Objective. Here, the frequency of Mediterranean Fever (MEFV) gene mutation and its effect on the outcome of IBD were evaluated. Methods. DNA sequence analysis detected the variants on the MEFV gene in patients with IBD. The relationship between mutations and the need for steroids, immunomodulators, biologics, and surgery was assessed. Results. We evaluated 100 patients with IBD (55 with ulcerative colitis (UC) and 45 with Crohn’s disease (CD)) and 60 healthy individuals as controls. The frequency of MEFV gene mutation was 26.7% (n=12) and 14.5% (n=8) for UC and CD, respectively. No relationship was found between MEFV gene mutation and the need for steroids, immunomodulators, and biologics (p=0.446;p=0.708;p>0.999, resp.); however, in UC, the need for surgery in those with mutation (p=0.018) and E148Q mutation alone was significant (p=0.037). Conclusion. The rate of MEFV gene mutations was high in patients with UC who required surgery. These patients have frequent and severe attacks, indicating that the mutations are related to disease severity. MEFV mutation as a modifier factor of IBD should be considered.